2014
DOI: 10.1007/s11661-014-2650-1
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Field Simulations and Analysis of Effect of Dispersed Particles on Migration of Delta to Gamma Transformation Interface

Abstract: Retardation effect of dispersed inert particles on delta-gamma interface migration in carbon steels during isothermal delta to gamma transformation is analyzed by two-dimensional phase-field simulations. The effect is systematically investigated for different values of particle radius, r, particle spacing, l, and initial carbon concentration of delta phase. The retardation effect becomes stronger when the pinning parameter described by r/l 2 is larger and the carbon concentration of delta phase is higher, indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
3
9
0
Order By: Relevance
“…The existence of the retardation effect was found in our previous study on isothermal d to c transformation by a diffusion-couple experiment [3]. In addition, two-dimensional phase-field simulations were carried out to investigate the details of this retardation effect [3,4]. It was shown that the retardation effect becomes stronger with the increase in a parameter, r/l 2 , where r is the size and l is the spacing of the particles.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…The existence of the retardation effect was found in our previous study on isothermal d to c transformation by a diffusion-couple experiment [3]. In addition, two-dimensional phase-field simulations were carried out to investigate the details of this retardation effect [3,4]. It was shown that the retardation effect becomes stronger with the increase in a parameter, r/l 2 , where r is the size and l is the spacing of the particles.…”
Section: Introductionmentioning
confidence: 77%
“…The detailed explanation of this model can be found in several articles [13][14][15] and our previous paper [4]. We will briefly explain the model here.…”
Section: Multi-phase-field Modelmentioning
confidence: 99%
See 3 more Smart Citations